2015
DOI: 10.1007/jhep11(2015)087
|View full text |Cite
|
Sign up to set email alerts
|

Finite coupling corrections to holographic predictions for hot QCD

Abstract: Finite 't Hooft coupling corrections to multiple physical observables in strongly coupled N = 4 supersymmetric Yang-Mills plasma are examined, in an attempt to assess the stability of the expansion in inverse powers of the 't Hooft coupling λ. Observables considered include thermodynamic quantities, transport coefficients, and quasinormal mode frequencies. Although large λ expansions for quasinormal mode frequencies are notably less well behaved than the expansions of other quantities, we find that a partial r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 97 publications
5
66
0
Order By: Relevance
“…This was discussed in Ref. [36] (see also [72]). Thus, it may be tempting to conclude with various speculations regarding the boundedness of quantities (or their ratios) considered in this work, such as an expectation that as a function of the coupling constant, v B (λ = g 2 Y M N c → ∞, N c ) ≤ v B (λ, N c ) ≤ 1, with v B → 1, monotonically, as g Y M → 0.…”
Section: Discussionmentioning
confidence: 76%
“…This was discussed in Ref. [36] (see also [72]). Thus, it may be tempting to conclude with various speculations regarding the boundedness of quantities (or their ratios) considered in this work, such as an expectation that as a function of the coupling constant, v B (λ = g 2 Y M N c → ∞, N c ) ≤ v B (λ, N c ) ≤ 1, with v B → 1, monotonically, as g Y M → 0.…”
Section: Discussionmentioning
confidence: 76%
“…This implies that those higher derivative terms can only be studied perturbatively, to avoid the emergence of instabilities, ghosts and other pathologies. Within this limit, these types of corrections have been vigorously studied in the past, exploring the correction of many different quantities (see [41] for a recent compilation of results). Recently, the relaxation of small stress tensor fluctuations in the thermal ensemble of N = 4 SYM has been studied in detail [42,43], (see also [44,45] for previous studies).…”
Section: Jhep04(2018)042mentioning
confidence: 99%
“…The regime of weak coupling can be described by the kinetic theory, while the transition from weak to strong coupling, i. e., the regime of intermediate coupling is not yet understood. Recently, an approach allowing one to obtain corrections to the regime of infinite coupling has been suggested in [10][11][12][13]. There it is shown that higher curvature corrections to the gravitational action, such as the GaussBonnet, Lovelock, R 4 or other terms, may give us a hint on what happens in the regime of intermediate coupling.…”
Section: Jhep09(2017)139mentioning
confidence: 99%